The Concept of Legal Nihilism and Measures to Prevent it among Youth (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article reveals the concept of legal nihilism, its causes, solutions for elimination, and various problems related to education.